The Relationship between Anti-dsDNA Antibody Levels and Clinical Manifestation in Systemic Lupus Erythematosus Patients - Noviantoro Sunarko; Ayu Paramaiswari; Deddy Nur Wachid Achadiyono (Indonesian Rheumatology Association, 2022)
Background: Anti-double-stranded deoxyribonucleic acid (anti-dsDNA) antibodies have been long known as specific autoantibodies in systemic lupus erythematosus (SLE) patients. Their central role in the pathogenesis of SLE also had been proposed for a long time. But many studies have failed to show a consistent association between anti-dsDNA levels and clinical manifestation in SLE patients. This phenomenon raised controversies about anti-dsDNA’s role in the development of the disease. This study aimed to give more description of the relationship between anti-dsDNA antibodies level and clinical manifestation of SLE. Methods: This study took place in Dr. Sardjito General Hospital, Yogyakarta, Indonesia, from July 2017 to July 2020. This study is a descriptive-analytic study with a cross-sectional design. Sixty-three females with new cases of SLE were included in this study. We used Alegria® ORGENTEC ORG204S kits to measure anti-dsDNA antibody levels in those patients. All organ involvement and anti-dsDNA level data were collected from the subject’s medical record. We categorized the patient into two groups, one group with a high level of anti-dsDNA antibodies and the other with the normal one. The statistical analysis was conducted by using the chi-square test to associate the anti-dsDNA antibodies level with the clinical manifestation of SLE that developed in those patients. Results: The haematological manifestation was the most prevalent clinical manifestation of SLE (69.8%), followed by cutaneous (66.7%) and musculoskeletal manifestation (63.5%), respectively. Thirty subjects had a high level of anti-dsDNA, and 33 subjects had the normal one. Anti-dsDNA antibody levels were only significantly associated with the development of haematological manifestation (p=0.026). Conclusion: Haematological manifestation tends to develop in SLE patients with high anti-dsDNA antibody levels.